Public health impact and return on investment of the pediatric National Immunization Program in Italy - Marco Barbieri; Sandra E. Talbird; Justin Carrico; Sara Boccalini; Angela Bechini; Paolo Bonanni; Claire E. Mellott; Francesca Senese; John Cameron Lang; Goran Bencina (Expert Review of Vaccines, 2024)
Objectives We conducted a cost–benefit analysis of the pediatric National Immunization Program (NIP) in Italy.Methods An economic model evaluated the benefit–cost ratio (BCR) of the Italian pediatric NIP, including 10 pathogens for mandatory vaccines and 4 pathogens for recommended vaccines for children aged 0–10 years from the healthcare-sector and societal perspectives. Separate decision trees were used to model each vaccine-preventable disease (VPD). The 2020 birth cohort (n = 420,084) was followed over their lifetime; the model projected and compared discounted disease cases, life-years, quality-adjusted life-years (QALYs), and costs (2021 euros) with and without immunization (based on current and pre – vaccine era disease incidence estimates, respectively).Results The pediatric NIP was estimated to prevent 1.8 million cases of VPDs and 3,330 deaths, resulting in 45,900 fewer life-years lost and 57,000 fewer QALYs lost. Vaccination costs of €285 million were offset by disease cost savings of €1.6 billion, resulting in a BCR of 5.6 from a societal perspective (BCR = 1.7 from a healthcare-sector perspective). When QALYs gained were valued, the BCR increased to 15.6.Conclusions The benefits of the Italian pediatric NIP, including averted disease-related morbidity, mortality, and associated costs, highlight the value of continued investment in pediatric immunization.